Diffusion‐weighted imaging outside the brain: Consensus statement from an ISMRM‐sponsored workshop. Issue 3 (19th February 2016) - Taouli, Bachir; Beer, Ambros J.; Chenevert, Thomas; Collins, David; Lehman, Constance; Matos, Celso; Padhani, Anwar R.; Rosenkrantz, Andrew B.; Shukla‐Dave, Amita; Sigmund, Eric; Tanenbaum, Lawrence; Thoeny, Harriet; et al.
Abstract : The significant advances in magnetic resonance imaging (MRI) hardware and software, sequence design, and postprocessing methods have made diffusion‐weighted imaging (DWI) an important part of body MRI protocols and have fueled extensive research on quantitative diffusion outside the brain, particularly in the oncologic setting. In this review, we summarize the most up‐to‐date information on DWI acquisition and clinical applications outside the brain, as discussed in an ISMRM‐sponsored symposium held in April 2015. We first introduce recent advances in acquisition, processing, and quality control; then review scientific evidence in major organ systems; and finally describe future directions. J. Magn. Reson. Imaging 2016;44:521–540.